Matéria escura e a anomalia do momento magnético do múon no modelo U(1)Lµ−Lτ - João Pedro Carvalho Corrêa (2022)
There are at least two open problems in elementary particle physics that challenge our understanding of the composition and fundamental interactions in the universe. The first is evidence for the existence of a different type of matter, known as Dark Matter, and the second is the disagreement between the experimental and theoretical predicted value of the muon’s magnetic moment, known as the g −2 muon anomaly. Both problems can be solved by considering an extension of the gauge symmetry group of electroweak interactions of the Standard Model to the symmetry SU(2)L⊗U(1)L⊗U(1)Lµ−Lτ. The key ingredient to solve these two problems is that the considered model has a neutral and stable fermionic particle, which produces an abundance of dark matter relics according to the experiments. This particle couples to the Standard Model particles through a gauge boson Z′ that makes an extra contribution to the muon’s g − 2 anomaly. In this way, both problems are connected in this model. In this thesis we study how couplings and model masses can be fixed using recent experimental results. In doing so, we conclude that the masses of dark matter and boson Z ′ are in the range of 1 − 50 MeV, which gives us a minimal solution to these puzzling problems. Finally, the model also gives us a contribution to ∆Neff that can relieve the tension on the Hubble constant.